Effect of lemongrass (Cymbopogoncitratus) essential oil on cardiac autonomic function in female Generalized Anxiety Disorder:A poincaré analysis of heart rate variability - Chowdhury, Esha; Sultana, Shamima; Morshed, Nahid Mahjabin; Zaman, Nusrut; Boby, Farjana (Journal of Bangladesh Society of Physiologist, 2024)
Background:Generalized anxiety disorder (GAD) is a worldwide, one of most prevalent mental disorder and associated with autonomic dysfunction. Poincaré plot of heart rate variability (HRV) is anonlinear method to assess cardiac autonomic nerve function (CANF).Lemongrass (Cymbopogoncitratus) essential oil (LEO) has been reported with anxiolytic effect and autonomic improvement in human. Objective: To assess the effect of LEO inhalation on CANF in female patients with GAD by analysis of poincaré plot of HRV.Method: This Quasi experimental study was conducted on 60 newly diagnosed female GAD patients with 20-40 years of age. Among them, 30 patients were treated with LEO inhalation for 15 min for once a week for one month (30days)along conventional treatment and 30 patients were without LEO inhalation and continued only conventional treatment for 30days.Thirty (30) apparently healthy subjects were control group.HRV data of all patients and control were recorded at baseline and after 30days of intervention or follow up respectively. HRV was recorded by a data acquisition device, Power Lab 8/35 and Poincaré plot analysis was done by lab chart software. For statistical analysis ANOVA followed by post-hoc test and paired sample ‘t’ test were done.Results: In this study, at baseline, the standard deviation of the short-term RR interval variability (minor axis of the cloud, SD1),the standard deviation of the long-term RR interval variability (major axis of the cloud, SD2) and SD1/SD2 were found significantly lower (p<0.001) in all GAD patients compared to control group. After 30 days of intervention with LOE, significant increase of SD1(p<0.001) and SD2, SD1/SD2 (p<0.01) were found in GAD patients whereas no significant difference was found in patients without LEO after 30 days. Moreover, significantly higher values of SD1 and SD2 were observed in GAD patients after aroma therapy with LEO compared to GAD patients not under aroma therapy. Furthermore, LEO could restore the BP of the GAD to the control level. Conclusion: This study concluded that, aromatherapy with LEO inhalation may be effective to improve cardiac autonomic dysfunction in female GAD patients. J Bangladesh Soc Physiol 2023;18(1): 19-26